Health Education Tentang jajanan Sehat Pada Anak Pra Sekolah di RA AL-MA’UNAH Desa Mojojejer Mojowarno Kabupaten Jombang - Ratnaningsih, Tri Ratnaningsih; Siti Indatul Laili; Tri Peni (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2023)
Pre-school age children are a period when children tend to be more active and energetic. They need good nutrition in addition to energy from food to support their growth and development as well as their daily activities. Consuming a balanced diet ensures that their nutritional needs are met. A balanced diet also helps children stay healthy and develop good eating habits, which will form a solid foundation for their future health. Snacks or food in the school environment sometimes does not guarantee the cleanliness and nutritional content of these snacks. Diseases that occur as a result of unhealthy snacking behavior can lead to health problems such as cancer, poisoning, food borne disease as well as growth and development disorders in health at the age of preschool children. The location for implementing community service is at RA AL-MA'UNAH, Mojojejer Village, Mojowarno Regency, Jombang Regency, where to meet the snack needs of students at RA AL-MA'UNAH, Mojojejer Village, Mojowarno Regency, Jombang Regency, they buy snacks from newcomers and regular sellers. Students before going to school and at 09.00 WIB when taking a break buy these snacks even though the teachers always suggest bringing their own food from home. The purpose of implementing this community service activity is that RA AL-MA'UNAH students in Mojojejer Village, Mojowarno Regency, Jombang Regency understand the importance of healthy snacks while at school so that they are used to living healthy after school through health education on healthy snacks by the Community Service team from Bina Sehat university PPNI Regency. Mojokerto. The method we use in community service is Health education about healthy snacks for RA AL-MA'UNAH students, Mojojejer Village, Mojowarno, Jombang Regency. The result of this health education is that RA AL-MA'UNAH, Mojojejer Village, Mojowarno, Jombang Regency, is able to understand and implement buying healthy snacks at school and at their respective homes.